وحدة دراسية مقترحة لتعليم العربية لموظفي الشريعة في البنوك الإسلامية في ماليزيا - Nor Zahidah binti Ahmad (Kulliyyah of Languages and Management, International Islamic Universiti Malaysia, 2017)
This study attempts to discover characteristics of the academic unit or module that suits teaching the Arabic language for shari'ah officers working in Islamic banks in Malaysia. This is based on special priorities and needs, analysed through the interviews that were held with five officers (four male and one female). The study was conducted using the method of descriptive analysis in order to collect the desired data. Then, the data was used to design a prototype of academic unit, which are as follows: the feel of mastering the Arabic language for their career, and usage of the language. In addition, the respondents are in dire need of Islamic banking and finance terms. Hence, the four language skills have to be added in the lessons with a greater focus on reading and writing in accordance with the respondent's grasp of the language. Based on the findings by the researcher, an Arabic language module for shari'ah officers is recommended.